2017
DOI: 10.1111/jfbc.12404
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic analysis of minimax and Williams 82 soybeans grown under two different conditions

Abstract: MiniMax was developed as a model soybean for research because of its small stature, limited planting space, and rapid generation time. In the present study, the proteins, isoflavones, and fatty acid methyl esters (FAMEs) were compared between dwarf (MiniMax) and commercially cultivated (Williams 82) soybean genotypes under two growing conditions (greenhouse and field). The protein profile of the soybean extracts by 2D‐PAGE showed at least 16 of 716 spots that were differently expressed in MiniMax and Williams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…In our study, the amounts of TP and TF were higher in field plants mostly with oven-dried samples than in those grown in the greenhouse, a finding that differs from that of John et al (2016) in which different varieties of soybean grown in a greenhouse (22.2 °C; photoperiod of up to 16 h) produced higher yields of isoflavones (daidzin, genistin, glycitein, daidzein and genistein) than plants grown in the field (21.7 °C; natural photoperiod). Moreover, when soybeans were cultivated in the field and the greenhouse under similar conditions of temperature and photoperiod, the accumulation of proteins and isoflavones remained higher in the greenhouse plants (John et al, 2017). The discrepancy between these results and those presented herein may be explained by differences in species and tissues analyzed and/or by differences in growing conditions in the field and in the greenhouse that prevailed in our study.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In our study, the amounts of TP and TF were higher in field plants mostly with oven-dried samples than in those grown in the greenhouse, a finding that differs from that of John et al (2016) in which different varieties of soybean grown in a greenhouse (22.2 °C; photoperiod of up to 16 h) produced higher yields of isoflavones (daidzin, genistin, glycitein, daidzein and genistein) than plants grown in the field (21.7 °C; natural photoperiod). Moreover, when soybeans were cultivated in the field and the greenhouse under similar conditions of temperature and photoperiod, the accumulation of proteins and isoflavones remained higher in the greenhouse plants (John et al, 2017). The discrepancy between these results and those presented herein may be explained by differences in species and tissues analyzed and/or by differences in growing conditions in the field and in the greenhouse that prevailed in our study.…”
Section: Discussioncontrasting
confidence: 92%
“…A number of studies have shown that growing conditions (field or greenhouse) exert significant effects on the content of primary and secondary metabolites in soybean seeds (John et al, 2016(John et al, , 2017. In our study, the amounts of TP and TF were higher in field plants mostly with oven-dried samples than in those grown in the greenhouse, a finding that differs from that of John et al (2016) in which different varieties of soybean grown in a greenhouse (22.2 °C; photoperiod of up to 16 h) produced higher yields of isoflavones (daidzin, genistin, glycitein, daidzein and genistein) than plants grown in the field (21.7 °C; natural photoperiod).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction was accompanied by downregulation of the expression of two legumin genes during seed development. In addition, in soybean, the abundance of several seed storage proteins was reported to vary considerably depending on whether genotypes were grown in the field or a glasshouse, indicating changes in protein composition due to prevailing conditions during seed growth. Therefore, better characterization of seed development and accumulation patterns of different storage proteins is the first step toward the rational modification of seed protein composition through genetics or agronomic practices.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of these pressures will influence the physiological response of plants. Furthermore, different organs or cultivars of soybean plants respond differently to the same stress, and the plant’s metabolic system is a constantly changing network of interconnections [ 2 , 96 , 97 ]. Nevertheless, the study of the soybean metabolome paves the way to a better understanding of complex metabolic pathways and stress-associated metabolites.…”
Section: Application Of Metabolomics As a Prospective Tool To Improve...mentioning
confidence: 99%